Study Fenomenologi Pengalaman Perawat Dalam Memberikan Asuhan Keperawatan Pada Pasien Covid-19 - Mila Triana Sari; Miko Eka Putri; Daryanto Daryanto (Universitas Batanghari Jambi, 2021)
Corona virus has caused 3 major disease outbreaks in the world over the last 2 decades, namely SARS, MERS, and Covid-19. The high number of cases of the corona virus has led to an increase in the number of patients in hospitals. Nurses are health workers who have the most frequent contact with patients, and have challenges to continue to provide professional nursing care at the risk of contracting or becoming a victim of Covid-19. This study aims to identify the experiences of nurses while caring for patients with Covid-19. This study is a qualitative research with a phenomenological approach that was carried out at the Jambi City Hospital from September 2020 to August 2021. The population in this study was nurses who served at the Covid-19 referral hospital. The sampling technique was purposive sampling with 13 participants, data collection was done by in-depth interviews, via telephone, and observation. The data collected were analyzed by the Creswell method. Based on the results of the study, five themes were obtained, namely Knowledge about Covid-19, Loyalty in caring for Covid-19 patients, Attention to caring for Covid-19 patients, Efforts to reduce the risk of Covid-19 transmission, and support from hospital management and families for nurses. The conclusion of this study is that the professionalism of nurses remains the main thing in treating Covid-19 patients even though nurses are overshadowed by feelings of fear and anxiety when treating Covid-19 patients. Efforts that need to be made are training related to the latest Covid-19 health care services, family and social support, as well as mentoring and improving the spirituality of nurses.